Intervenciones de enfermería para la aplicación del plan canguro en el servicio de neonatología del Hospital General Delfina Torres De Cocha - Mafla Pantoja, Diego Roberto (2019)
The aim of thia research study was to develop nursing practices for the application v7 Dre marernal Kargaros Plan in the Veonatology service al lhe General Hospital Esmeraldas Delfina Torres”. The modality of study was qualitative nd yuantitativo which allowed to make sn analysis and interpretation of the results oblained. A survey was conducicd to 23 professional nurses who work in the nconatology area so it was possible Lo collect dato and real information. Among the main results, it was found Mal 60% of the nuesing professionals conld identify the cbaracleristics of the maternal Kangaroo Plen. le is worth adding chat the methodology used was descriprive, correlational and ironsversal ax well as some methuda such as historic-lugic and analytical -ayathictio which led to a hetler understanding of the current problem. This was Une hass for the proposal development 1 vrder to focus vn Ike paticotis cure improvoment. Thercíorc, he results are meant (0 enhance tho quality and the awareness Of nursing practicos $0 thal hey ensure the benofits addressed direcuy to the nevnáate*3 care.